Pengembangan E-Module Berbasis Inkuiri Terbimbing Pada Materi Sistem Reproduksi Manusia Terintegrasi Keislaman Kelas XI - Khasanah, Purnama Uswatun; Nirmalasari, Ridha; Lestariningsih, Nanik; Ayatusa'adah, Ayatusa'adah (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: An educator must have expertise in developing teaching materials that can support and assist students in the learning process. One of the teaching materials that educators can develop is in the form of e-modules. This research aims to develop and create a teaching material product in the form of an e-module based on guided inquiry on the Islamic integrated human reproductive system material in class XI for Senior High School/MA. Method: The type of research used in this research is in the form of R&D (Research and Development), or what can be called research and development; the development model used is ADDIE. The ADDIE development model has several stages: Analysis, Design, Development, Implementation, and Evaluation. Research data was collected by validating e-module products, observing learning implementation, and using questionnaires from educators' and students' responses. The data from this analysis trial uses descriptive quantitative data. Product trials were conducted using small-scale tests in class XI MIPA 5 MAN Palangka Raya City. Results: E-modules developed to obtain material expert validation assessments have 91% results that fall into the